2018
DOI: 10.1111/jnp.12145
|View full text |Cite
|
Sign up to set email alerts
|

Hemispatial neglect and serial order in verbal working memory

Abstract: Working memory refers to our ability to actively maintain and process a limited amount of information during a brief period of time. Often, not only the information itself but also its serial order is crucial for good task performance. It was recently proposed that serial order is grounded in spatial cognition. Here, we compared performance of a group of right hemisphere-damaged patients with hemispatial neglect to healthy controls in verbal working memory tasks. Participants memorized sequences of consonants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The hypothesis that the momentum effect in temporal arithmetic reflects a genuinely intrinsic spatial component is consistent with previous results showing that temporal duration processing can be affected by a variety of visuospatial manipulations, including prismatic adaptation (Frassinetti et al, 2009), reverse reading (Casasanto &Bottini, 2014), andvisuospatial priming (Di Bono et al, 2012). Furthermore, neuropsychological studies on patients affected by contralesional space disorders reveal a systematic association between pathological visuospatial processing and conceptual time in the form of ordered events processing (Antoine et al, 2019;Bonato et al, 2016, see Rinaldi et al, 2018 on the impact of purely visual impairment). Both lines of evidence (normal and pathological) therefore converge in suggesting that some aspects of time representation (either sensory or conceptual) are spatial in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that the momentum effect in temporal arithmetic reflects a genuinely intrinsic spatial component is consistent with previous results showing that temporal duration processing can be affected by a variety of visuospatial manipulations, including prismatic adaptation (Frassinetti et al, 2009), reverse reading (Casasanto &Bottini, 2014), andvisuospatial priming (Di Bono et al, 2012). Furthermore, neuropsychological studies on patients affected by contralesional space disorders reveal a systematic association between pathological visuospatial processing and conceptual time in the form of ordered events processing (Antoine et al, 2019;Bonato et al, 2016, see Rinaldi et al, 2018 on the impact of purely visual impairment). Both lines of evidence (normal and pathological) therefore converge in suggesting that some aspects of time representation (either sensory or conceptual) are spatial in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the right intraparietal sulcus was suggested as a neural correlate with the ability to represent the serial order of linguistic elements [41,42]. Lesion studies seem to confirm the involvement of the right parietal cortex in a verbal working memory task, in which the serial order of memorized consonants had to be recognized [43].…”
Section: Reduction Of Transposition Errors During Right Anodal Stimul...mentioning
confidence: 84%
“…The neural substrate of this distinction has been identified at the level of the left and right intraparietal sulcus [41,42]. Recently, Antoine and colleagues [43] reported that patients affected by hemispatial neglect with lesions to the right parietal posterior cortex produced more order errors than item errors in a verbal working memory task, compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential information is organized in either time or space, which are compatible (Fischer-Baum and Benjamin, 2014). Serial-order memory is highly connected with spatial working memory, and sequence information is represented in the form of space (van Dijck et al, 2013;Antoine et al, 2018).…”
Section: Introductionmentioning
confidence: 99%